2019
DOI: 10.4049/jimmunol.1800976
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Diabetogenic Immunity by IL-15–Activated Regulatory CD8 T Cells in Type 1 Diabetes

Abstract: Unchecked collaboration between islet-reactive T and B lymphocytes drives type 1 diabetes (T1D). In the healthy setting, CD8 T regulatory cells (Tregs) terminate ongoing T-B interactions. We determined that specific CD8 Tregs from NOD mice lack suppressive function, representing a previously unreported regulatory cell deficit in this T1D-prone strain. NOD mice possess 11-fold fewer Ly-49 + CD8 Tregs than nonautoimmune mice, a deficiency that worsens as NOD mice age toward diabetes and leaves them unable to reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In addition to abovementioned EAE model (19,36,37), CD8 + CD122 hi Ly49 + Tregs have documented functions in various settings, including colitis (38,39), hepatitis (40), arthritis (41), diabetes (42,43), viral infection (44), tumor immunity (45), atherogenesis (46) and organ transplantation (47). The best demonstrated role of CD8 + Tregs is to suppress GC reaction.…”
Section: Cd122 Hi Ly49 + Cd8 + Treg -Discovery and Functionmentioning
confidence: 99%
“…In addition to abovementioned EAE model (19,36,37), CD8 + CD122 hi Ly49 + Tregs have documented functions in various settings, including colitis (38,39), hepatitis (40), arthritis (41), diabetes (42,43), viral infection (44), tumor immunity (45), atherogenesis (46) and organ transplantation (47). The best demonstrated role of CD8 + Tregs is to suppress GC reaction.…”
Section: Cd122 Hi Ly49 + Cd8 + Treg -Discovery and Functionmentioning
confidence: 99%
“…Despite these initial reports, it became clear that CD122 is not suitable as a standalone marker for mouse and human CD8 + Treg cells, as it is upregulated in memory‐phenotype and antigen‐experienced cells [38–42]. For these reasons, some researchers proposed additional or alternative markers of the CD8 + CD122 + population such as CD44 [43, 44], CD62L [44], CXCR3 [38], PD‐1 [44, 45], CD38 [46], and Ly49 [43, 47, 48]. It is also clear that CD8 + CD122 + T cells overlap, at least partially, with antigen inexperienced memory‐like T (AIMT) cells (alias virtual memory T cells), that is, CD8 + T cells that have memory phenotype despite no previous antigen exposure [42, 49, 50].…”
Section: Cd8+ Cd122+ T Cellsmentioning
confidence: 99%
“…The regulatory capacities of CD8 + CD122 + T cells have been documented in models of experimental colitis, experimental autoimmune encephalomyelitis (EAE) and autoimmune diabetes [48, 51, 52]. These experiments showed that CD8 + CD122 + T cells are able to prevent the development of an autoimmune disease or ameliorate its symptoms, but did not fully enlighten the underlying mechanisms.…”
Section: Cd8+ Cd122+ T Cellsmentioning
confidence: 99%
“…93 This finding led to the treatment of NOD mice with adoptively transferred IL-15-activated CD8 + Tregs, which resulted in delayed diabetes onset. 93 Notably, IL-15-mediated Foxp3 expression in CD4 + Tregs could be abrogated by IL-15-activated NK cells. 92 The results of these studies show that IL-15 can accelerate T1D in vivo and, more importantly, also regulates diabetogenic effects via activation of Tregs, which, however, may be eliminated by simultaneous activation of diabetogenic T cells and NK cells.…”
Section: Il-15mentioning
confidence: 99%
“…IL‐15 is required for the development of Ly49 + CD8 + Tregs, whose deficiency is increased with ageing, as NOD mice progress towards diabetes (Figure 1 and Table 1). This finding led to the treatment of NOD mice with adoptively transferred IL‐15‐activated CD8 + Tregs, which resulted in delayed diabetes onset . Notably, IL‐15‐mediated Foxp3 expression in CD4 + Tregs could be abrogated by IL‐15‐activated NK cells .…”
Section: New Players In the T1d Cytokine Milieumentioning
confidence: 99%